Defects and Bäcklund transformations for the N=1 supersymmetric mKdV hierarchy - Spano, Nathaly Infantini [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
A integrabilidade da hierarquia de Korteweg de-Vries modificada supersimétrica com N=1 (smKdV) na presença de defeitos é investigada através da construção de sua transformação de Bäcklund supersimétrica. A construção de tal transformação é realizada usando essencialmente dois métodos: a abordagem da matriz de defeito e empregando o operador de recursão. Primeiramente, empregamos a matriz de defeitos associada à hierarquia, que é a mesma para o modelo sinh-Gordon supersimétrico (sshG). O método é geral e válido para todos os fluxos da hierarquia e como exemplo derivamos explicitamente as equações de Bäcklund para os primeiros fluxos, são eles t_1, t_3 e t_5. Em segundo lugar, o operador de recursão relacionando tempos consecutivos é derivado e mostrados que ele relaciona também as transformações de Bäcklund. Finalmente, esta transformação de Bäcklund supersimétrica é empregada para introduzir defeitos do tipo I para a hierarquia supersimétrica mKdV. Outros aspectos de integrabilidade são considerados, através da construção das quantidades conservadas modificadas, derivadas da matriz de defeito.

The integrability of the N=1 supersymmetric modified Korteweg de-Vries (smKdV) hierarchy in the presence of defects is investigated through the construction of its super Bäcklund transformation. The construction of such transformation is performed by essentially using two methods: the Bäcklund-defect matrix approach and the by employing the recursion operator. Firstly, we employ the defect matrix associated to the hierarchy which turns out to be the same for the supersymmetric sinh-Gordon (sshG) model. The method is general for all flows and as an example we derive explicitly the Bäcklund equations in components for the first few flows of the hierarchy, namely t_1, t_3 and t_5. Secondly, the recursion operator relating consecutive time flows is derived and shown to relate their Bäcklund transformations. Finally, this super Bäcklund transformation is employed to introduce type I defects for the supersymmetric mKdV hierarchy. Further integrability aspects by considering modified conserved quantities are derived from the defect matrix.
Defeitos e transformações de Bäcklund para a hierarquia mKdV Supersimétrica com N=1
Keywords: Integrable hierarchies; Bäcklund transformations; integrable defects; smKdV